Historical Construction of Local Islamic Culture in Central Kalimantan: Bibliographic Study of Islamic History Writing - Santi, Selvia (NALAR, 2024)
The growth of local Islamic history literature is important as an effort to provide more detailed insights from national Islamic history. This study aims to understand the writing of local Islamic history in Central Kalimantan by conducting a bibliographic investigation through scientific papers related to the history of Islam in Central Kalimantan. The results of this study contribute to showing how far efforts have been made to reconstruct local Islamic history. The object of this research is government institutions and educational institutions in the Central Kalimantan region, especially the West Kotawaringin region and the city of Palangka Raya. The local history works found will be categorized into several divisions. Data then analyzed using social and historical analysis to see the influence of the growth of social history in Central Kalimantan on the growth of local history literature. Through social and historical analysis, scientific works in the form of papers, research reports, theses, and books in the last few years after the development of the Central Kalimantan province through the establishment of educational and cultural institutions showed a significant increase in the number of scientific works. Based on bibliographic searches, it is known that the growth in the number of local Islamic history papers is directly proportional to the social development of the people of Central Kalimantan province. This research aims to show efforts to write local Islamic history in Central Kalimantan.